An Analysis Of Adjectival Construction On Michael Buble's Album "To Be Loved 2013" - Sunyoto, Bekti, Dra. Malikatul Laila, M. Hum, Dra. Siti Zuhriah Ariatmi, M. Hum (2015)
This study aims at explaining and describing the forms and the distributions of adjectival construction on Michael Buble's album (to be loved 2013). The techniques of data collection are: reading the album of Michael Buble, underlying for the adjectival construction in the album, rewriting the data and coding the data. This research method used is descriptive qualitative as the type of research.The object of this study is adjectival construction analysis of data found in Michael Buble's album. The whole data which are found by the researcher are 68 sentences containing AdjP construction. The result shows that there are two forms: simple and complex AdjP Construction. Simple AdjP Constructionsare subdivided into four subdivisions: noun, verb, adjective and adverb. Complex AdjP Constructionsare subdivided into six subdivisions: Noun Phrase (NP), Adjective Phrase (AP), Verb Phrase (VP), Adverb Phrase (AdvP), Preposition Phrase (PP) and Adjective Clause (AC). There are 3 distributions of English AdjPconstruction: (1) pre modifier, (2) post modifier, and (3) pre and post modifier. There are many songs are in Michael Buble's album. So, this research can help the listener or the reader to understand the content of the songs. Keywords: syntax, phrase, adjectival construction.